Low Cost Portable Ventilator with Pressure Regulation using Arduino - Shibitha KP; Thasni Fathima S; Arya V; Karthika Satheesh K T; Fathima Nihala P (Journal of Electronic Design Engineering, 2022)
The patient is suffering from an injury or illness that makes it hard to breathe. A ventilator may help to breathe during these conditions. It is useful in surgery where you are asleep, but this is usually for no more than a few hours. So simply ventilator is a machine that helps a patient to breathe when they are having a surgery or cannot breathe their own due to a critical illness. That. That is why the device is more important in hospitals .Here the patient is connected to the ventilator with a hollow tube that goes in their mouth and down into their main airway or trachea. In this paper develops a portable ventilator using AMBU (Artificial Manual Breathing Unit) Bag. The pressure and volume of air passed to the patient from the ventilator can be measured using sensors and the readings can be displayed using Android app. The count, pressure and volume of air passed to the patient from the ventilator can be measured using relevant sensors and the readings can be displayed in both LCD display and Android app. The controlling of pressure is also possible with the help of Android app. The main advantages of this ventilator are that it is less expensive, portable and also automatically works. In emergency conditions the doctor can adjust the amount of air using a control mechanism that is built in Android application .Also if the Doctor is not there a will be a notification sent to telegram of the Doctor or the hospital health assistant, and people around are alerted by the buzzer if pressure increases.